Drania Własne i Wymuszone Pewnego Typu Płyt Wzmocnionych Żebrami - Mikołajczyk, H. (Engineering Transactions, 1962)
The solution concerns orthotropic plates simply supported along two parallel edges with ribs normal to these edges, The problem of natural and forced vibration is solved. The excitation is assumed to be concentrated with no mass, pulsating with the frequency p, the attachment point moving with constant velocity along a rib. Time dependent forces in the plane of the plate are taken into consideration, The mass forces in this plane are rejected. The ribs are assumed to be one-sided, constituting a monolithic system with the plate. The torsional rigidity of the plate is accounted for as well as the material damping which is assumed in the complex form. The method of simple Fourier series is used. In conclusion, two numerical examples are given, the influence of various simplifications being analysed. The results are represented in the form of tables and graphs.